Bibliometric Analysis: Trend of Digital Literacy and Scientific Literacy Research in Indonesia Biology Learning - Trisnawati, Eka (JURNAL BIOEDUKATIKA, 2023)
This study aims to analyze research trends related to digital literacy and scientific literacy in Indonesia biology learning and find future research opportunities. The method used is a literature review with bibliometric analysis. The bibliometric analysis utilizes the Google Scholar database, sourced from Journals and Proceedings with a publication period of 2012-2022 Search for articles used PoP application and bibliometric mapping used VOSviewer. The results of analysis obtained 18 articles related to digital literacy, 100 articles related scientific literacy, and 1 article related to both. The most cited research is related to the use of learning models to increase scientific literacy. The mapping results obtained 2 clusters with 17 items. Research about digital literacy and scientific in Indonesia biology learning began to be widely in 2019-2022. Research on digital literacy and literacy in biology learning is still very much in demand at this time. Digital literacy in biology learning in Indonesia is still rarely studied. In conclusion, research related to digital literacy and scientific literacy is still a research trend in biology learning in Indonesia today. Digital literacy is still rarely researched and can be used as an opportunity in the future in research in the field of biology education.